Plan de negocio para la comercialización de banano orito (Musa Acuminata) recinto Manguila Chico, cantón La Maná, año 2015 - De la Guerra Pilco, Luz Mayra (2015)
The current investigation project was held at the Campus Manguila Chico, belonging to the Parroquia El Carmen, the Canton La Mana, Cotopaxi Province. Orito banana producers remain inadequate enclosure marketing techniques which affects profitability and satisfaction thereof. The main objective of the research is to design a business plan for the commercialization of orito banana (Musa acuminata) during 2015; for which the descriptive literature deductive and analytical methods used. By SWOT analysis weaknesses such as lack of technical training for producers, the lack of proper planning and control in the financial area was evident; Through surveys it was determined that there is dissatisfaction of the producers regarding the income received; and a high percentage of cases that are exported at a price below the established price; this because the producers have not signed a contract with the distributors, to ensure stability of prices and quotas throughout the year. By market study it showed that in the year 2014 126.088 boxes were exported to international market; Therefore it is recommended to socialize and implement the proposals to improve the production and marketing of bananas in the enclosure orito Manguila Chico; thus contributing to the development of the Canton La Mana and country.